2017
DOI: 10.1002/pssr.201700144
|View full text |Cite
|
Sign up to set email alerts
|

Highly‐efficient superstrate Cu2ZnSnS4 solar cell fabricated low‐cost methods

Abstract: Phone: þ54 223 481 6600, Fax: þ54 223 481 0046 A recent accomplishment in the preparation of a highly efficient thin film solar cell is reported. This superstrate cell is composed of FTO/TiO 2 /In 2 S 3 /Cu 2 ZnSnS 4 /graphite. A maximum conversion efficiency of 3.5% has been achieved for the first time using this configuration and materials. The device includes low cost methods and nontoxic components. Details of the experimental procedures are provided and the device characterization data are presented and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Details of precursorsolutions preparation can be found elsewhere. 46,49,50 The TiO 2 layer was deposited over a hot plate at 350 • C, spraying 10 cycles of 20 s of duration with 60 s pauses between cycles. After the deposition process, the samples were maintained at 450 • C on the hot plate during 60 min and cooled at room temperature.…”
Section: Cell Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of precursorsolutions preparation can be found elsewhere. 46,49,50 The TiO 2 layer was deposited over a hot plate at 350 • C, spraying 10 cycles of 20 s of duration with 60 s pauses between cycles. After the deposition process, the samples were maintained at 450 • C on the hot plate during 60 min and cooled at room temperature.…”
Section: Cell Preparationmentioning
confidence: 99%
“…Two spin coating cycles were used and, between the cycles a 10 min thermal treatment at 150 • C was used. Finally a second 10 minutes thermal treatment was performed at 250 • C. 46,49,50 The final architecture of the cell is observed in Figure 10. The electrical contacts were painted with conductive graphite ink (Alpha Aesar).…”
Section: Cell Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…They used ntype and top electrode as In 2 S 3 and graphite. 5 Yan et al found an efficiency of 2.15% for CZTS in superstrate configuration; they incorporated a P3HT layer into a p-type layer with a Cu electrode. 6 Tumbul et al revealed the efficiency of a solar cell with superstrate type CZTS as 0.7%.…”
Section: Introductionmentioning
confidence: 99%
“…Berruet M et al reported that the efficiency of the CZTS superstrate type as 3.5 %. They used n-type and top electrode as In 2 S 3 and graphite [5]. Yan R et al found the efficiency of 2.15 % for CZTS in superstrate configuration; they incorporated the P3HT layer into the p-type layer with Cu electrode [6].…”
Section: Introductionmentioning
confidence: 99%